THE MEDIATING ROLE OF BRAND LOYALTY AND ALLEGIANCE IN THE RELATIONSHIP BETWEEN BRAND VALUE AND PURCHASING IN WHITE GOODS INDUSTRY (Third Sector Social Economic Review, 2023)
In this study, besides determining the effect of brand value on purchasing behavior in the white goods sector, it is also aimed to determine the mediating role of brand loyalty and brand loyalty in the relationship between brand value and purchasing behavior. The sampling consisting of 732 data selected with the convenience sampling method was reached by face-to-face and online survey methods. In addition to the fact that brand value has a direct effect on consumers' purchasing behavior, it is considered that loyal and brand-affiliated customers also recommend products and services they are satisfied with and their brands to their circles, and increase the awareness of the brand through word of mouth communication and advertise it. In this way, new customers are brought to the brand and the continuity of the continuous purchasing behavior of loyal customers is increased. With these results, it has been supported that businesses and marketers should include strategies for brand loyalty and loyalty along with activities to increase brand value in their strategies.
Keywords: Brand Value; Brand Loyalty; Brand Commitment; White Goods